Penetration of zona-free hamster, bovine and equine oocytes by stallion and bull spermatozoa pretreated with equine follicular fluid, dilauroylphosphatidylcholine or calcium ionophore A23187 - Landim-Alvarenga, F. C.; Alvarenga, Marco Antonio [UNESP]; Seidel, G. E.; Squires, E. L.; Graham, J. K. (Elsevier B.V., 2001)
Experiments evaluated the ability of follicular fluid (FF), dilauroylphosphatidylcholine (PC12) and the calcium ionophore A23187 (A23187) to induce capacitation in stallion and bull spermatozoa, determined by the ability of the spermatozoa to penetrate zona-free hamster, bovine and equine oocytes. Spermatozoa suspensions were incubated at 37 degreesC in one of the following treatments: 1) a modified Tyrode's medium (BGM3) alone, 2) BGM3 + FF; 3) BGM3 + PC12; 4) BGM3 + FF + PC12; 5) BGM3 + A23187; and 6) BGM3 + FF + A23187. Treated spermatozoa were incubated with zona-free hamster, bovine and equine oocytes for 3 h, after which oocytes were stained to assess spermatozoa penetration. The number of hamster oocytes penetrated by spermatozoa incubated in BGM3 alone (1/30) or in presence of FF (2/31) was significantly lower (P < 0.05) than by spermatozoa treated with PC12 or A23187 (16/30 and 17/30, respectively). Processing stallion spermatozoa either by a swim-up procedure or by centrifugation through a Percoll gradient increased the percentages of motile spermatozoa in the final sample, and spermatozoa collected by both processes penetrated similar numbers of zona-free hamster oocytes (P > 0.05). Although treating spermatozoa with PC12 or A23187 enabled both stallion and bull spermatozoa to penetrate oocytes, higher numbers of bovine oocytes were penetrated by bull spermatozoa (25/30) than by stallion spermatozoa (4/30) regardless of spermatozoal treatment. However, the number of zona-free hamster and equine oocytes penetrated by bull spermatozoa (25/30 and 12/18 respectively) and stallion spermatozoa (17/30 and 15/21 respectively) were similar (P > 0.05). We conclude that both PC12 and A23187 capacitate stallion and bull spermatozoa sufficiently to permit the acrosome reaction to occur, enabling spermatozoa to penetrate homologous and heterologous zona-free oocytes. (C) 2001 by Elsevier B.V.
Keywords: spermatozoa; capacitation; follicular fluid; dilauroylphosphatidylcholine; calcium ionophore; equine